Tissue bonding patch and preparation method thereof

By setting a reinforcement layer in the tissue adhesive patch and using specific copolymers in the adhesive layer to form an interpenetrating network structure, the problems of insufficient adhesion and poor mechanical properties of existing tissue adhesives are solved, and stronger adhesion and mechanical properties are achieved, and antibacterial properties are achieved.

CN119524188AActive Publication Date: 2025-02-28SICHUAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411764151.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-28
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Existing tissue adhesives have problems with insufficient adhesiveness and poor mechanical properties.

Method used

By providing a reinforcement layer in the tissue adhesive patch and copolymerizing succinimide acrylate with acrylate or N-isopropyl acrylamide substances and quaternary ammonium cationic monomers in the adhesive layer, an interpenetrating network structure is formed to enhance the cohesion and wet adhesion of the adhesive.

Benefits of technology

It significantly improves the bonding strength and mechanical properties of the tissue adhesive patch, enhances its bonding effect on the wet tissue surface and dry tissue surface, and has good antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168461670000081
    Figure BDA0005168461670000081
  • Figure HDA0005168461680000011
    Figure HDA0005168461680000011
  • Figure HDA0005168461680000012
    Figure HDA0005168461680000012
Patent Text Reader

Abstract

The invention discloses a tissue adhesive patch and a preparation method thereof, relates to the technical field of medical materials, and solves the technical problems of insufficient adhesive force and poorer mechanical property of the existing tissue adhesive. The composite material comprises a bonding layer and a reinforcing layer, the bonding layer is coated on the surface of the enhancement layer and is photocured to form a tissue bonding patch; the raw material of the reinforcing layer is a degradable polyester material; the raw materials of the bonding layer comprise a component A, a component B, a component C and a component D; the component A is a degradable high polymer material; the component A is acrylic acid ester or N-isopropyl acrylamide, and the component B is acrylic acid ester or N-isopropyl acrylamide; the component C is succinimide acrylate, and the component D is a quaternary ammonium salt cationic monomer containing unsaturated double bonds; through the arrangement of the reinforcing layer, the effect of reinforcing and toughening the bonding patch is achieved, and meanwhile the bonding strength of the bonding patch is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical materials, and in particular to a tissue adhesive patch and a preparation method thereof. Background Art

[0002] Commonly used methods for repairing wounds or fistulas on the surface of visceral tissues in clinical practice include bonding with tissue glue or stapler-assisted anastomosis of fistulas. Commonly used tissue adhesives include α-cyanoacrylate, fibrin glue, etc. α-cyanoacrylate has strong adhesion, but after bonding, it has high hardness, poor toughness, poor tissue mechanics matching, and poor biocompatibility, and is prone to toxic side effects. Fibrin glue is an adhesive extracted from human plasma, mainly containing fibrinogen, thrombin, etc. Its curing reaction directly utilizes the body's own coagulation mechanism, and ultimately generates a fibrin network with strong adhesion, but there are risks of poor wet surface adhesion, immunogenicity, and viral infection.

[0003] Some existing technologies also use hydrogels as adhesives to bond and repair tissues. They have good biocompatibility and are available in a variety of forms to adapt to complex tissues. However, practice has found that hydrogel adhesives have insufficient adhesion and their mechanical properties cannot meet usage requirements. Summary of the invention

[0004] The present invention aims to solve the technical problems of insufficient adhesion and poor mechanical properties of existing tissue adhesives, and aims to provide a tissue adhesive patch and a preparation method thereof, which can enhance the toughness of the adhesive patch by setting a reinforcing layer, and at the same time improve the bonding strength of the adhesive patch.

[0005] The present invention is achieved through the following technical solutions:

[0006] A first object of the present invention is to provide a tissue adhesive patch, comprising an adhesive layer and a reinforcing layer;

[0007] The adhesive layer is coated on the surface of the reinforcement layer and light-cured to form a tissue adhesive patch;

[0008] The raw material of the reinforcing layer is a degradable polyester material;

[0009] The raw materials of the adhesive layer include component A, component B, component C and component D;

[0010] The component A is a degradable polymer material;

[0011] The component B is acrylate or N-isopropylacrylamide;

[0012] The component C is succinimidyl acrylate;

[0013] The component D is a quaternary ammonium salt cationic monomer containing an unsaturated double bond.

[0014] Furthermore, the component A is selected from any one or more combinations of polyvinyl pyrrolidine, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl methyl cellulose, sodium alginate, gelatin, gum arabic, and gum tragacanth.

[0015] Furthermore, the component A is selected from any one or more combinations of polyvinyl alcohol and polyvinyl pyrrolidone.

[0016] Furthermore, the acrylic acid ester is selected from any one or more combinations of hydroxyethyl methacrylate, hydroxyethyl acrylate, and hydroxybutyl acrylate.

[0017] Furthermore, the acrylic acid esters are selected from hydroxyethyl acrylate.

[0018] Furthermore, the raw material of the reinforcement layer is selected from any one or more combinations of PLGA, PLA, PGA, PCL, PPDO, PHA, PHB and PHV.

[0019] Furthermore, the component D is selected from any one or more combinations of acryloyloxyethyl trimethyl ammonium chloride, methacryloyloxyethyl trimethyl ammonium chloride, methacrylamide propyl trimethyl ammonium chloride and alkyl allyl ammonium chloride.

[0020] Furthermore, the adhesive layer also includes active ingredients that can be loaded to promote tissue healing, and the active ingredients include recombinant human epidermal growth factor, fibroblast growth factor, and vascular endothelial cell growth factor.

[0021] A second object of the present invention is to provide a method for preparing a tissue adhesive patch, comprising the following steps:

[0022] Dissolving a degradable polyester material in an organic solvent to form a degradable polyester solution; coating the degradable polyester solution on a template to form a layer of degradable polyester liquid film; placing the coated template in a vacuum drying oven for drying, and forming a reinforcement layer after drying;

[0023] The raw materials of the adhesive layer, component A, a degradable polymer material, component B, acrylates or N-isopropylacrylamide, component C, succinimidyl acrylate, and component D, a quaternary ammonium salt cationic monomer containing an unsaturated double bond, are dissolved in distilled water, a water-soluble photoinitiator is added and stirred to dissolve to form a prepolymer solution, the prepolymer solution is coated on the reinforcement layer, and the solution is placed in a UV curing box for curing for 0.5-3 hours, and a tissue adhesive patch is formed after curing.

[0024] Furthermore, the dissolution concentration of the degradable polyester material is 3%-20%, the dissolution concentration of component A is 5%-20%, the dissolution concentration of component B is 10%-35%, the dissolution concentration of component C is 3-15%, and the dissolution concentration of component D is 1%-15%.

[0025] Furthermore, the amount of the water-soluble photoinitiator added is 0.05-0.1% of the total mass of the solution, and the water-soluble photoinitiator is selected from α-hydroxyketone water-based photoinitiators.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] 1. The present invention utilizes succinimidyl acrylate to copolymerize with acrylate or N-isopropenyl acrylamide and quaternary ammonium salt cationic monomers to form an adhesive body, and forms an interpenetrating network structure with a degradable polymer material to enhance the cohesive force of the adhesive body. Succinimidyl acrylate can react with amine groups on the tissue surface under physiological conditions to form strong amide covalent bonds; the introduction of quaternary ammonium salt cationic monomers can react with negatively charged functional groups on the tissue surface, such as OH groups. - 、COOO - etc. to form a strong electrostatic force interaction, provide non-covalent bonding adhesion, and further enhance the wet adhesion of the adhesive; at the same time, the polar groups in the degradable polymer material can also form strong hydrogen bonds and van der Waals forces with the tissue surface, providing partial adhesion, so that the tissue adhesive patch provided by the present invention has stronger adhesion.

[0028] 2. The quaternary ammonium salt introduced into the tissue adhesive patch of the present invention has good broad-spectrum bactericidal properties, so that the tissue adhesive patch has strong adhesion and certain antibacterial properties, which can effectively prevent wound infection.

[0029] 3. The present invention polymerizes and cures the adhesive prepolymer solution on the reinforcing layer under the action of ultraviolet light. The free radical polymerization reaction will prompt the group part in the adhesive to be grafted on the reinforcing layer, so that the adhesive layer and the reinforcing layer are firmly combined together. Therefore, through the provision of the reinforcing layer, the mechanical strength and toughness of the adhesive layer are enhanced, thereby improving the mechanical properties of the patch. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0031] Figure 1 It is a schematic diagram of the structure of the tissue adhesive patch of the present invention;

[0032] Figure 2 This is a product picture of the tissue adhesive patch prepared in Example 5 of the present invention;

[0033] Figure 3 This is the lap-shear adhesion strength curve of the tissue adhesive patch prepared in Example 5 of the present invention;

[0034] Figure 4 This is the peel strength curve of the tissue adhesive patch prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the technical solutions in the embodiments of the present invention are clearly and completely described below in combination with the embodiments and drawings. Obviously, the schematic implementation modes of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0036] The following is a detailed description of an embodiment of a tissue adhesive patch and a method for preparing the same according to the present invention with reference to the accompanying drawings as appropriate. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions and repeated descriptions of well-known matters are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art.

[0037] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0040] Unless otherwise specified, the terms "include" and "comprising" mentioned in this application may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other substances not listed may also be included or only the listed substances may be included.

[0041] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.

[0042] In order to solve the technical problems of insufficient adhesion and poor mechanical properties of existing tissue adhesives, the technical solution of the present invention is to provide a tissue adhesive patch, the structure of which is as follows Figure 1 As shown, comprising an adhesive layer and a reinforcing layer;

[0043] The adhesive layer is coated on the surface of the reinforcement layer and light-cured to form a tissue adhesive patch;

[0044] The raw material of the reinforcing layer is a degradable polyester material;

[0045] The raw materials of the adhesive layer include component A, component B, component C and component D;

[0046] The component A is a degradable polymer material;

[0047] The component B is acrylate or N-isopropylacrylamide;

[0048] The component C is succinimidyl acrylate;

[0049] The component D is a quaternary ammonium salt cationic monomer containing an unsaturated double bond.

[0050] The present invention utilizes succinimidyl acrylate to copolymerize with acrylate or N-isopropenyl acrylamide substances and quaternary ammonium salt cationic monomers to form an adhesive body, and forms an interpenetrating network structure with a degradable polymer material to enhance the cohesive force of the adhesive body. Succinimidyl acrylate can react with amine groups on the tissue surface under physiological conditions to form strong amide covalent bonds; the introduction of quaternary ammonium salt cationic monomers can react with negatively charged functional groups on the tissue surface, such as OH groups. - 、COOO - etc. to form a strong electrostatic interaction, providing non-covalent bonding adhesion, further enhancing the wet adhesion of the adhesive; at the same time, the polar groups in degradable polymer materials such as PVP can also form strong hydrogen bonds and van der Waals forces with the tissue surface, providing partial adhesion.

[0051] The adhesive prepolymer solution is polymerized and cured on the reinforcing layer under the action of ultraviolet light. The free radical polymerization reaction will cause the group part in the adhesive to be grafted on the reinforcing layer, so that the adhesive layer and the reinforcing layer are firmly combined together. Specifically, under the action of the ultraviolet light initiator, the free radicals generated by the carbon-carbon double bonds of the acrylate or quaternary ammonium salt cationic monomer in the adhesive component react with the hydroxyl group in the reinforcing layer polyester to connect together, so that the adhesive layer and the reinforcing layer are more firmly combined together. Therefore, by setting the reinforcing layer, the mechanical strength and toughness of the adhesive layer are enhanced, and the mechanical properties of the patch are improved. In actual use, the mechanical strength of the patch can be adjusted by adjusting the concentration of the reinforcing layer to meet the requirements of different tissues for mechanical strength, so as to facilitate better bonding between the adhesive layer and the tissue.

[0052] The tissue adhesive patch provided by the present invention can be bonded on a wet tissue surface or on a dry tissue surface after the patch is moistened with water, and has a strong bonding force. After the surface of the adhesive patch contacts water, the water is rapidly absorbed by the water-absorbing components therein, so that the dry adhesive layer forms a sticky gel, and at the same time, the water on the tissue surface is removed, which is conducive to the reaction between the adhesive groups in the adhesive and the tissue surface groups to form strong adhesion.

[0053] The tissue adhesive patch of the present invention is used to repair various tissue wounds or fistulas, such as skin surface wounds, as an adhesive patch for various visceral tissue wounds, such as heart, liver, kidney, and gastrointestinal tract and blood vessels, and can also be used in conjunction with repair tools such as intestinal staplers to reinforce the anastomosis. The patch has good mechanical flexibility and can adapt to the normal physiological peristalsis of the tissue without being torn.

[0054] In one or more embodiments, the component A is selected from any one or more combinations of polyvinyl pyrrolidine, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl methyl cellulose, sodium alginate, gelatin, gum arabic, and gum tragacanth. Preferably, the component A is selected from any one or more combinations of polyvinyl alcohol and polyvinyl pyrrolidone.

[0055] In one or more embodiments, the acrylic ester is selected from any one or more combinations of hydroxyethyl methacrylate, hydroxyethyl acrylate, and hydroxybutyl acrylate. Preferably, the acrylic ester is selected from hydroxyethyl acrylate.

[0056] In one or more embodiments, the raw material of the reinforcement layer is selected from any one or more combinations of PLGA, PLA, PGA, PCL, PPDO, PHA, PHB and PHV.

[0057] In one or more embodiments, the component D is selected from any one or more combinations of acryloyloxyethyl trimethyl ammonium chloride, methacryloyloxyethyl trimethyl ammonium chloride, methacrylamide propyl trimethyl ammonium chloride and alkyl allyl ammonium chloride.

[0058] In order to expand the function of the tissue adhesive patch of the present invention, active ingredients that promote tissue healing, including but not limited to recombinant human epidermal growth factor, fibroblast growth factor, vascular endothelial growth factor, etc., can also be loaded during the preparation of the adhesive layer.

[0059] Based on the above tissue adhesive patch, the present invention also provides a method for preparing a tissue adhesive patch, comprising the following steps:

[0060] Dissolving a degradable polyester material in an organic solvent to form a clear and transparent solution, with a concentration of 3%-20%, preferably 5-10%, to form a degradable polyester solution; using a spin coater to coat the degradable polyester solution on a polytetrafluoroethylene template to form a layer of degradable polyester liquid film, the spin coating parameters are: rotation speed 80-400r / min, acceleration 20-100m / s, spin coating time 10-40s; then putting the coated template into a vacuum drying oven for drying, the drying parameters are: time 10-40min, pressure -0.5-0.01Mpa, temperature 30-80℃; after drying, a reinforcement layer is formed;

[0061] The raw materials of the bonding layer, component A, a degradable polymer material, component B, acrylate or N-isopropylacrylamide, component C, succinimidyl acrylate, and component D, a quaternary ammonium salt cationic monomer containing an unsaturated double bond, are dissolved in distilled water to form a clear and transparent solution, a water-soluble photoinitiator is added and stirred to dissolve to form a prepolymer solution, and the prepolymer solution is coated on the reinforcing layer by a spin coating machine, and the spin coating parameters are: rotation speed 80-400r / min, acceleration 20-100m / s, spin coating time 10-40s, and placed in a UV curing box (60w, 365nm) for curing for 0.5-3h. After curing, the formed membrane is removed from the template to obtain a tissue bonding patch.

[0062] In one or more embodiments, the dissolution concentration of the degradable polyester material is 3%-20%, preferably 5-10%, the dissolution concentration of component A is 5%-20%, the dissolution concentration of component B is 10%-35%, the dissolution concentration of component C is 3-15%, and the dissolution concentration of component D is 1%-15%. The organic solvent is selected from any one of hexafluoroisopropanol, ethyl formate, ethyl acetate, toluene, and dichloromethane.

[0063] In one or more embodiments, the amount of water-soluble photoinitiator added is 0.05-0.1% of the total mass of the solution. Specifically, the water-soluble photoinitiator is selected from α-hydroxyketone water-based photoinitiators, such as Irgacure2959, Irgacure651, etc., preferably Irgacure2959.

[0064] The technical solution of the present invention is further described in detail below in conjunction with embodiments.

[0065] It should be noted that the experimental methods used in the examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained by those skilled in the art through commercial channels.

[0066] Example 1

[0067] Preparation of reinforcement layer

[0068] Dissolve PCL in dichloromethane to form a clear solution with a concentration of 8%. Use a spin coater to coat the PCL solution on a polytetrafluoroethylene mold to form a layer of PCL liquid film, with a rotation speed of 80r / min and a rotation time of 10s. The mold after spin coating is placed in a vacuum drying oven and dried for 30 minutes to remove the dichloromethane solvent to obtain a patch enhancement layer with a thickness of 300um.

[0069] Example 2

[0070] Preparation of reinforcement layer

[0071] PCL was dissolved in hexafluoroisopropanol to form a clear solution with a concentration of 10%. The PCL solution was coated on a polytetrafluoroethylene mold using a spin coater to form a layer of PCL liquid film at a rotation speed of 100 r / min and a rotation time of 12 s. The mold after spin coating was placed in a vacuum drying oven and dried for 35 min to remove the hexafluoroisopropanol solvent to obtain a patch reinforcement layer with a thickness of 200 um.

[0072] Example 3

[0073] Preparation of reinforcement layer

[0074] PCL was dissolved in hexafluoroisopropanol to form a clear solution with a concentration of 15%. The PCL solution was coated on a polytetrafluoroethylene mold using a spin coater to form a layer of PCL liquid film at a rotation speed of 100 r / min and a rotation time of 15 s. The mold after spin coating was placed in a vacuum drying oven and dried for 40 min to remove the hexafluoroisopropanol solvent to obtain a patch enhancement layer with a thickness of 150 um.

[0075] Example 4

[0076] Preparation of reinforcement layer

[0077] PLGA and PCL were dissolved in hexafluoroisopropanol to form a mixed solution with a concentration of 10% and a ratio of PLGA:PCL = 3:7. The mixed solution was coated on a polytetrafluoroethylene mold using a spin coater to form a liquid film at a rotation speed of 100 r / min and a rotation time of 12 s. The mold after spin coating was placed in a vacuum drying oven and dried for 35 min to remove the hexafluoroisopropanol solvent to obtain a patch enhancement layer with a thickness of 220 um.

[0078] Example 5

[0079] The tissue adhesive patch was prepared by using the product prepared in Example 1 as the patch reinforcement layer.

[0080] The raw materials of each component were dissolved in distilled water to form a homogeneous prepolymer solution, the concentrations of which were 10% polyvinyl pyrrolidone, 10% hydroxyethyl acrylate, 10% succinimidyl acrylate, 6% acryloyloxyethyl trimethyl ammonium chloride, and 0.5% Irgacure 651 initiator. The prepolymer solution was applied to the mold of the PLGA reinforcement layer by spin coating. The reinforcement layer was placed under a 365nm ultraviolet lamp for photocuring for 2 hours to obtain a tissue adhesive patch.

[0081] Example 6

[0082] The tissue adhesive patch was prepared by using the product prepared in Example 1 as the patch reinforcement layer.

[0083] The raw materials of each component were dissolved in distilled water to form a homogeneous prepolymer solution, with concentrations of 15% polyvinyl alcohol, 15% hydroxyethyl methacrylate, 12% succinimidyl acrylate, 8% methacrylamide propyl trimethylammonium chloride, and 1.0% Irgacure 2959 initiator. The prepolymer solution was applied to the mold of the PCL reinforcement layer by spin coating. The reinforcement layer was placed under a 365nm ultraviolet lamp for photocuring for 1.5 hours to obtain a tissue adhesive patch.

[0084] Example 7

[0085] The tissue adhesive patch was prepared by using the product prepared in Example 1 as the patch reinforcement layer.

[0086] The raw materials of each component were dissolved in distilled water to form a homogeneous prepolymer solution, with concentrations of 12% hydroxypropyl methylcellulose, 10% N-isopropyl acrylamide, 5% succinimidyl acrylate, 10% dimethyl diallyl ammonium chloride, and 0.8% Irgacure 651 initiator. The prepolymer solution was applied to the mold of the PLGA reinforcement layer by spin coating. The reinforcement layer was placed under a 365nm ultraviolet lamp for photocuring for 1 hour to obtain a tissue adhesive patch with a thickness of 500um.

[0087] Comparative Example 1

[0088] The tissue adhesive patch was prepared by the method of Example 5, except that the adhesive layer did not contain component D.

[0089] Comparative Example 2

[0090] The tissue adhesive patch was prepared by the method of Example 5, except that it did not contain a reinforcement layer.

[0091] The properties of the tissue adhesive patches prepared in Examples 5-7 of the present invention and the comparative examples were tested. The test results are shown in Table 1.

[0092] (1) Burst pressure test

[0093] Take a cleaned fresh pig small intestine, about 15 cm in length, clamp one end of the small intestine with surgical forceps, and insert the other end into a CO 2 The silicone hose of the gas is closed and fixed with a cable tie. The silicone hose is equipped with a high-precision pressure test gauge for testing the bursting pressure. A 2mmx2mm rupture is made in the middle of the small intestine, and the adhesive patch is cut into a 10mmx10mm square. The cut patch is moistened with saline and attached to the rupture of the small intestine. After pressing for 10 minutes, the CO 2 The air source is used to ventilate the small intestine at a rate of 2 mL / s, and the maximum pressure during the whole process is recorded as the bursting pressure of the tissue patch.

[0094] (2) Lap-shear tensile strength test

[0095] Fresh pigskin was degreased according to Appendix 2, and then cut into strips of length x width x thickness = 60 mm x 25 mm x 2 mm. The tissue patch was cut into strips of the same length and width. The pigskin and the front end of the adhesive layer of the tissue patch were overlapped 25 mm x 10 mm, and pressed for 30 minutes after overlap. The test was carried out according to the method of ASTM F2255, and the data was collected to calculate the shear strength of the interface.

[0096] (3) Peel strength test, interface toughness

[0097] After degreasing, fresh pigskin was cut into strips of length x width x thickness = 60 mm x 25 mm x 2 mm, and the tissue patch was cut into strips of the same length and width. The pigskin was bonded to the adhesive layer of the adhesive patch, and pressed for 30 minutes after bonding. The test was performed according to the ASTM F2256 method, and the data was collected to calculate the peel strength of the patch.

[0098] (4) Elongation at break

[0099] The tissue adhesive patch was cut into a size of 60 mm x 25 mm, and both ends of the patch were clamped and fixed on a universal testing machine with a clamp. The patch was stretched at a speed of 5 mm / min, and the elongation of the patch when it broke was recorded, and the elongation at break of the tissue patch was calculated.

[0100] (5) Antibacterial performance test

[0101] The extract of the adhesive layer in physiological saline was taken, and the test method referred to WS / T650-2019, and the antibacterial performance test was carried out on Staphylococcus aureus.

[0102] Table 1. Test results of the properties of tissue adhesive patches prepared in Examples 5-7 and Comparative Examples

[0103]

[0104] It can be seen from the data in Table 1 that the tissue adhesive patch prepared by the present invention has excellent bonding strength and peel strength, and effectively improves the mechanical properties of the patch compared to the adhesive patch without a reinforcement layer. After the quaternary ammonium salt is introduced into the tissue adhesive patch, its adhesion and antibacterial properties are significantly improved.

[0105] Finally, it should be noted that the above specific embodiments are only used to explain in detail the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific implementation method of the present invention and is not used to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above specific embodiments, ordinary technicians in this field should understand that it is still possible to modify the technical solutions recorded in the above embodiments, or to replace or improve some or all of the technical features therein. These modifications, equivalent replacements and improvements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention.

Claims

1. A tissue adhesive patch, characterized in that: including an adhesive layer and a reinforcing layer; The adhesive layer is coated on the surface of the reinforcement layer and light-cured to form a tissue adhesive patch; The raw material of the reinforcing layer is a degradable polyester material; The raw materials of the adhesive layer include component A, component B, component C and component D; The component A is a degradable polymer material; The component B is acrylate or N-isopropylacrylamide; The component C is succinimidyl acrylate; The component D is a quaternary ammonium salt cationic monomer containing an unsaturated double bond.

2. A tissue adhesive patch according to claim 1, characterized in that: The component A is selected from any one or more combinations of polyvinyl pyrrolidine, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl methyl cellulose, sodium alginate, gelatin, gum arabic, and gum tragacanth.

3. A tissue adhesive patch according to claim 2, characterized in that: The component A is selected from any one or more combinations of polyvinyl alcohol and polyvinyl pyrrolidone.

4. The tissue adhesive patch according to claim 1, characterized in that: The acrylic esters are selected from any one or more combinations of hydroxyethyl methacrylate, hydroxyethyl acrylate, and hydroxybutyl acrylate.

5. A tissue adhesive patch according to claim 4, characterized in that: The acrylic acid esters are selected from hydroxyethyl acrylate.

6. The tissue adhesive patch according to claim 1, characterized in that: The raw material of the reinforcement layer is selected from any one or more combinations of PLGA, PLA, PGA, PCL, PPDO, PHA, PHB and PHV.

7. A tissue adhesive patch according to any one of claims 1 to 6, characterized in that: The component D is selected from any one or more combinations of acryloyloxyethyl trimethyl ammonium chloride, methacryloyloxyethyl trimethyl ammonium chloride, methacrylamide propyl trimethyl ammonium chloride and alkyl allyl ammonium chloride.

8. A tissue adhesive patch according to any one of claims 1 to 6, characterized in that: The adhesive layer also includes active ingredients that can be loaded to promote tissue healing, and the active ingredients include recombinant human epidermal growth factor, fibroblast growth factor, and vascular endothelial cell growth factor.

9. A method for preparing a tissue adhesive patch according to any one of claims 1 to 8, comprising the following steps: Dissolving a degradable polyester material in an organic solvent to form a degradable polyester solution; coating the degradable polyester solution on a template to form a layer of degradable polyester liquid film; placing the coated template in a vacuum drying oven for drying, and forming a reinforcement layer after drying; The raw materials of the adhesive layer, component A, which is a degradable polymer material, component B, which is acrylates or N-isopropylacrylamide, component C, which is a substance containing catechol, and component D, which is a quaternary ammonium salt cationic monomer containing an unsaturated double bond, are dissolved in distilled water, and a water-soluble photoinitiator is added and stirred to dissolve to form a prepolymer solution. The prepolymer solution is coated on the reinforcement layer and placed in a UV curing box for curing for 0.5-3 hours. After curing, a tissue adhesive patch is formed.

10. The method for preparing a tissue adhesive patch according to claim 9, characterized in that: The dissolution concentration of the degradable polyester material is 3%-20%, the dissolution concentration of component A is 5%-20%, the dissolution concentration of component B is 10%-35%, the dissolution concentration of component C is 3-15%, and the dissolution concentration of component D is 1%-15%.

11. The method for preparing a tissue adhesive patch according to claim 9, characterized in that: The amount of the water-soluble photoinitiator added is 0.05-0.1% of the total mass of the solution, and the water-soluble photoinitiator is selected from α-hydroxyketone water-based photoinitiators.

Citation Information

Patent Citations

  • Single-sided adhesive hydrogel adhesive as well as preparation method and application thereof

    CN114306725A

  • Self-adhesive absorbable biological patch as well as preparation method and application thereof

    CN115814173A

  • Superstructure porous wet adhesive hydrogel as well as preparation method and application thereof

    CN116693931A

  • Self-adhesion tissue patch capable of promoting repair as well as preparation method and application of self-adhesion tissue patch

    CN117298335A

  • Multilayer structure tissue repair patch as well as preparation method and application thereof

    CN117695447A